2013
DOI: 10.2134/jeq2012.0341
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Diminishes Nitrous Oxide and Nitrate Leaching from Diverse Nutrient Sources

Abstract: Manure generated by intensive livestock operations poses potential ecological risk in the form of water pollution and greenhouse gas emission. To assess the impact of biochar on coarse-textured soils under contrasting nutrient management regimes, a 55-d incubation was conducted using unplanted soil columns amended with manure, slurry, or fertilizer (plus unamended control), each with or without biochar applied at 2% soil mass (dry weight basis). Under repeated leaching, the cumulative NO emission from the colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 48 publications
5
39
1
Order By: Relevance
“…Many studies that have suggested that biochar addition reduces the loss of NO 3 − -N via leaching or increases soil accumulation were conducted over relatively short incubation periods (days to months) (Novak et al, 2010;Angst et al, 2013;Eykelbosh, 2015;Xu et al, 2016) …”
Section: No 3 -N Can Biochar Provide Ammonium and Nitrate To Poor Soils?mentioning
confidence: 99%
“…Many studies that have suggested that biochar addition reduces the loss of NO 3 − -N via leaching or increases soil accumulation were conducted over relatively short incubation periods (days to months) (Novak et al, 2010;Angst et al, 2013;Eykelbosh, 2015;Xu et al, 2016) …”
Section: No 3 -N Can Biochar Provide Ammonium and Nitrate To Poor Soils?mentioning
confidence: 99%
“…Cayuela et al (2013) demonstrated that biochar increased soil pH and subsequently promoted the reduction of N 2 O to N 2 . Meanwhile, biochar could absorb soil NH 4 þ or NO 3 À , which in turn would decrease the availability of mineral N (Angst et al, 2013;Case et al, 2012;van Zwieten et al, 2010) and enhance soil aeration (Rogovska et al, 2011).…”
Section: Effects Of Biochar Addition On N 2 O and No Emissionsmentioning
confidence: 99%
“…Another potential mechanism for decreased N 2 O emissions in biochar-amended soils may be an increased adsorption of ammonium cations (NH + 4 ) and/or N-containing organic compounds, which reduce both N leaching and N 2 O emissions (Singh et al, 2010). While most studies have shown reductions in N 2 O emissions for soils amended with biochar relative to control soils (Angst et al, 2013;Cayuela et al, 2013), no significant differences and even small increases between biochar-amended soil and controls in N 2 O emissions have been reported (Karhu et al, 2011;Scheer et al, 2011).…”
Section: Biochar Characteristicsmentioning
confidence: 99%